Neurological Symptoms in Patients with Mild Combat Traumatic Brain Injury (Global Journal of Medical Research, 2020)
We evaluated 97 patients aged 23 to 37 years in the acute period of mild combat traumatic brain injury, prescription of which was from 2 to 5 days. We observed the loss of consciousness (from 5 to 20 minutes) in 39 individuals. We studied in detail the neurological status and state of the autonomic nervous system. We obtained the data that allowed to note the peculiarities of the disease course depending on the vector of action of the explosive injury with regard to the body side. Under the impact of the blast wave to one of the body sides we observed the following features as a nonspecific hemi syndrome, decreased of sensitivity to pain, decreased smell, decreased pain sensitivity on the tongue, decreased taste, hearing, decreased periosteal and tendon reflexes, decreased muscle strength and tonus on the side of the sensory defect, and when the direction of the blast is frontal (to the face), the clinical course of the disease is much more severe.
Keywords: acute combat traumatic brain injury; sensori motor nonspecific hemi syndrome; vegetative disorders; #x201C; sleep-waking#x201D; cycle disorders